2019
DOI: 10.1111/1747-0080.12513
|View full text |Cite
|
Sign up to set email alerts
|

Development of a diabetes‐related nutrition knowledge questionnaire for individuals with type 2 diabetes mellitus in Singapore

Abstract: Aim Diabetes‐related nutrition knowledge (DRNK) is essential for the self‐care of patients with type 2 diabetes mellitus (T2DM). A specific tool measuring DRNK can help us to understand awareness levels and tailor structured nutrition education programs. Our study aimed to develop a questionnaire to assess DRNK for individuals with T2DM in Singapore. Methods An expert panel was formed to consolidate in‐depth, culturally suitable, and current information on DRNK. A literature review of diabetes self‐care knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…We used a locally validated tool, the DRNK-Q, to assess the level of DRNK in our cohort. 20 The DRNK-Q consists of four sections and 27 questions related to the topics covered in dietetic therapy and education sessions for patients with T2DM: food portion and sizes; nutrition content of food; healthier food choices and safety; and food label reading. The DRNK-Q was completed before the patients were provided with further dietary advice to prevent contamination of results.…”
Section: Methodsmentioning
confidence: 99%
“…We used a locally validated tool, the DRNK-Q, to assess the level of DRNK in our cohort. 20 The DRNK-Q consists of four sections and 27 questions related to the topics covered in dietetic therapy and education sessions for patients with T2DM: food portion and sizes; nutrition content of food; healthier food choices and safety; and food label reading. The DRNK-Q was completed before the patients were provided with further dietary advice to prevent contamination of results.…”
Section: Methodsmentioning
confidence: 99%
“…Nine instruments were identified that were specifically designed to assess dietary knowledge in patients with DM type 1 or 2: the Diabetes Patient Knowledge Test (DPKT) (Hess & Davis, 1983), the Diabetes Knowledge Assessment Scale (DKN) (Dunn et al., 1984), and the Michigan Diabetes Knowledge Test (DKT) (Al Qahtani et al., 2016; Alhaiti et al., 2016; Al‐Qazaz et al., 2010; Collins et al., 2011; Fenwick et al., 2013; Fitzgerald et al., 1998, 2016; Hasan et al., 2019; İDİZ et al., 2020; Mangla et al., 2019; Sigurdardottir & Benediktsson, 2008), the Diabetes Knowledge Questionnaire (DKQ) (Ahmad et al., 2010; Bukhsh et al., 2017; Garcia et al., 2001; W. Sami et al., 2017), the Diabetes Knowledge Assessment Test (DKAT) (Weeks et al., 2015), the Personal Diabetes Questionnaire (PDQ) (Cheng et al., 2018; Stetson et al., 2011), the Diabetes Mellitus Knowledge (DMK) (W. Sami et al., 2017), the Conocidiet‐Diabetes (Brito‐Brito et al., 2020), and the Diabetes‐related Nutrition Knowledge (DRNK) (Han et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Different versions of the Michigan Diabetes Knowledge Test (Al Qahtani et al., 2016; Alhaiti et al., 2016; Al‐Qazaz et al., 2010; Collins et al., 2011; Fenwick et al., 2013; Fitzgerald et al., 1998, 2016; Hasan et al., 2019; İDİZ et al., 2020; Mangla et al., 2019; Sigurdardottir & Benediktsson, 2008), Diabetes Knowledge Questionnaire (Ahmad et al., 2010; Bukhsh et al., 2017; Garcia et al., 2001; W. Sami et al., 2017), and Personal Diabetes Questionnaire (Cheng et al., 2018; Stetson et al., 2011) were carried out, each of which varied in the number of items. Most of these studies were carried out in the hospital, community, and primary care settings, in patients with type 1 DM (Mangla et al., 2019; Sigurdardottir & Benediktsson, 2008), type 2 DM (Alhaiti et al., 2016; Al‐Qazaz et al., 2010; Bukhsh et al., 2017; Cheng et al., 2018; Fenwick et al., 2013; Garcia et al., 2001; Han et al., 2019; W. Sami et al., 2017), or type 1 and 2 DM (Al Qahtani et al., 2016; Brito‐Brito et al., 2020; Dunn et al., 1984; Fitzgerald et al., 1998, 2016; Hasan et al., 2019; Hess & Davis, 1983; İDİZ et al., 2020; Stetson et al., 2011; Weeks et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 2195 articles were excluded after evaluation. Subsequently, 22 full-text articles were evaluated, and 8 articles were excluded after reviewing the full text [ 11 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Thus, a total of 14 studies were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%